Effectiveness of orofacial myofunctional therapy in orthodontic patients: A systematic review - Márcio Alexandre Homem; Raquel Gonçalves Vieira-Andrade; Saulo Gabriel Moreira Falci; Maria Letícia Ramos-Jorge; Leandro Silva Marques (Dental Press Editora, 2014)
OBJECTIVE: The aim of the present systematic review was to determine the existence of scientific evidence demonstrating the effectiveness of orofacial myofunctional therapy (OMT) as an adjuvant to orthodontic treatment in individuals with orofacial disorders. A further aim was to assess the methodological quality of the studies included in the review. METHODS: An electronic search was performed in eight databases (Medline, BBO, LILACS, Web of Science, EMBASE, BIREME, Cochrane Library and SciELO) for papers published between January 1965 and March 2011, with no language restrictions. Selection of articles and data extraction were performed by two independent researchers. The quality of the selected articles was also assessed. RESULTS: Search strategy resulted in the retrieval of 355 publications, only four of which fulfilled the eligibility criteria and qualified for final analysis. All papers selected had a high risk of bias. CONCLUSIONS: The findings of the present systematic review demonstrate the scarcity of consistent studies and scientific evidence supporting the use of OMT in combination with orthodontic treatment to achieve better results in the correction of dentofacial disorders in individuals with orofacial abnormalities.